THE IMPACT OF COMMUNICATIVE ASPECT ON THE ELECTORAL CHOICE - Корнелюк, І. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the process of using the media in election campaigns. Since communication is a means of attracting people into political life through the perception of political information, involvement in the political processes taking place in society, and at the same time influencing electoral orientation of the population, it is important to analyze its influence on the electoral guidelines of citizens. That is why the article analyzes the interdependence of media influence and voter awareness with the indicators of competent, effective electoral choice and formation of determinants of electoral behavior. It is also important to emphasize the need to establish a mechanism of bilateral communication by the community and politicians in the electoral process. In the formation of a new system of values ​​and norms, political realities require the study of the electoral behavior of young people in society and the search for ways to increase the level of electoral activity, the introduction of effective electoral technologies, overcoming the political nihilism of citizens.